Role of Actin Cytoskeleton in Dynamics and Function of the Serotonin(1A) Receptor - Shrivastava, Sandeep (Biophys J, 2020)
G protein-coupled receptors (GPCRs) are important membrane proteins in higher eukaryotes that carry out a vast array of cellular signaling and act as major drug targets. The serotonin(1A) receptor is a prototypical member of the GPCR family and is implicated in neuropsychiatric disorders such as anxiety and depression, besides serving as an important drug target. With an overall goal of exploring the functional consequence of altered receptor dynamics, in this work, we probed the role of the actin cytoskeleton in the dynamics, ligand binding, and signaling of the serotonin(1A) receptor. We monitored receptor dynamics utilizing single particle tracking, which provides information on relative distribution of receptors in various diffusion modes in addition to diffusion coefficient. We show here that the short-term diffusion coefficient of the receptor increases upon actin destabilization by cytochalasin D. In addition, analysis of individual trajectories shows that there are changes in relative populations of receptors undergoing various types of diffusion upon actin destabilization. The release of dynamic constraint was evident by an increase in the radius of confinement of the receptor upon actin destabilization. The functional implication of such actin destabilization was manifested as an increase in specific agonist binding and downstream signaling, monitored by measuring reduction in cellular cAMP levels. These results bring out the interdependence of GPCR dynamics with cellular signaling.